Simultaneous proteasome and autophagy inhibition synergistically enhances cytotoxicity of doxorubicin in breast cancer cells. (29th April 2022) - Loh, Jian Sheng; Rahim, Nusaibah Abdul; Tor, Yin Sim; Foo, Jhi Biau
Abstract: Ubiquitin–proteasome system (UPS) and autophagy are interconnected proteolysis pathways implicated in doxorubicin resistance of breast cancer cells. Following anticancer treatments, autophagy either plays a cytoprotective role or augments treatment‐induced cytotoxicity. However, the role of autophagy in breast cancer cells cotreated with doxorubicin and ixazomib remains unclear. The expression of autophagy proteins (LC3A/B and Beclin‐1) and UPS protein (ubiquitin) in MDA‐MB‐231 and MCF‐7 cells following doxorubicin, ixazomib, and/or hydroxychloroquine were determined by western blot. The combinatorial effects and combination index (CI) of triple‐combination were determined by cell viability assay and CompuSyn software, respectively. Doxorubicin and ixazomib cotreatment increased Beclin‐1 (3.8‐ and 3.5‐fold) and LC3‐II expression (13.5‐ and 1.9‐fold) in MDA‐MB‐231 and MCF‐7 cells, respectively. Adding lysosomal inhibitor hydroxychloroquine to doxorubicin and ixazomib further increased LC3‐II expression to 45.0‐ and 16.5‐fold in MDA‐MB‐231 and MCF‐7 cells, respectively, confirming autophagy induction. The triple‐combination synergistically inhibited cell growth, achieving CI 0.672 and 0.157 in MDA‐MB‐231 and MCF‐7 cells, respectively. The triple‐combination also induced ubiquitinated proteins accumulation (2.5‐fold and 3.0‐fold) in MDA‐MB‐231 and MCF‐7 cells, respectively. These results suggest that the autophagy induced by doxorubicin and ixazomib cotreatment serves cytoprotective role in breast cancer cells. Simultaneous UPS and autophagy inhibition synergistically enhanced doxorubicin‐mediated cytotoxicity. Significance statement: This study shows that simultaneously inhibiting two protein degradation pathways, namely the ubiquitin‐proteasome system and autophagy, with clinically achievable concentration of ixazomib and hydroxychloroquine significantly impaired the ability of breast cancer cells to maintain protein homeostasis, evidenced by significant accumulation of toxic ubiquitinated proteins. The cytotoxicity of doxorubicin in triple‐negative breast cancer cells was synergistically and significantly enhanced by combined proteasome and autophagy inhibition. Ixazomib and hydroxychloroquine are clinically approved drugs with well‐established safety and toxicity profile. The strategy of drug repurposing potentially allows a cheaper, faster, and more accessible way to make drugs available to improve oncologic outcomes.